Retrograde nuclear transport from the cytoplasm is required for tRNATyr maturation in T. brucei - Kessler, Alan C; Kulkarni, Sneha S; Paulines, Mellie J; Rubio, Mary Anne T; Limbach, Patrick A; Paris, Zdeněk; Alfonzo, Juan D (RNA biology, 2018)
Retrograde transport of tRNAs from the cytoplasm to the nucleus was first described in Saccharomyces cerevisiae and most recently in mammalian systems. Although the function of retrograde transport is not completely clear, it plays a role in the cellular response to changes in nutrient availability. Under low nutrient conditions tRNAs are sent from the cytoplasm to nucleus and presumably remain in storage there until nutrient levels improve. However, in S. cerevisiae tRNA retrograde transport is constitutive and occurs even when nutrient levels are adequate. Constitutive transport is important, at least, for the proper maturation of tRNAPhe, which undergoes cytoplasmic splicing, but requires the action of a nuclear modification enzyme that only acts on a spliced tRNA. A lingering question in retrograde tRNA transport is whether it is relegated to S. cerevisiae and multicellular eukaryotes or alternatively, is a pathway with deeper evolutionary roots. In the early branching eukaryote Trypanosoma brucei, tRNA splicing, like in yeast, occurs in the cytoplasm. In the present report, we have used a combination of cell fractionation and molecular approaches that show the presence of significant amounts of spliced tRNATyr in the nucleus of T. brucei. Notably, the modification enzyme tRNA-guanine transglycosylase (TGT) localizes to the nucleus and, as shown here, is not able to add queuosine (Q) to an intron-containing tRNA. We suggest that retrograde transport is partly the result of the differential intracellular localization of the splicing machinery (cytoplasmic) and a modification enzyme, TGT (nuclear). These findings expand the evolutionary distribution of retrograde transport mechanisms to include early diverging eukaryotes, while highlighting its importance for queuosine biosynthesis.
Keywords: buněčné jádro; transport RNA; Trypanosoma brucei brucei; Cell Nucleus; Active Transport, Cell Nucleus; RNA Splicing; RNA Transport; cytoplazma; Saccharomyces cerevisiae; Nucleic Acid Conformation; nukleosid Q; Pentosyltransferases; Kinetics; kinetika; pentosyltransferasy; RNA transferová Phe; Cytoplasm; Nucleoside Q; RNA, Transfer, Phe; sestřih RNA; RNA transferová Tyr; aktivní transport - buněčné jádro; konformace nukleové kyseliny; RNA, Transfer, Tyr